Парадигмальне проектування: світоглядний рівень - Федь, В. (Схід, 2011)
У статті виконано теоретичне осмислення проблеми парадигми в культурософському аспекті. Показано, що саме культурна парадигма здатна перевести фокус знань людини про
світ за горизонт, у царину евристичного, культуротворчо осмисленого існування людини. На
думку автора, за такої умови духовного розвитку людини можлива поява адекватних відповідей на злободенні проблеми сучасності. In the article there is presented the theoretical understanding of the problem of paradigm in the cultural-philosophic
aspect. It is the cultural paradigm that is able to transfer the focus of the knowledge of any man behind the horizon, into
the sphere of something heuristic, the cultural creativ ely understood existence of any man. In the author's opinion
under such a condition of the spiritual development of any man the appearance of the adequate answers to the urgent
problems of the mankind is possible.